2022
DOI: 10.1029/2022gl100294
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal‐Interannual Predictions of Summer Precipitation Over the Tibetan Plateau in North American Multimodel Ensemble

Abstract: Variations of precipitation over the Tibetan Plateau (TP) have great hydrometeorological impacts on local and surrounding areas. Focusing on the TP precipitation in the boreal summer, this study investigates the seasonal‐interannual predictions of eight dynamical models from the North‐American Multi‐Model Ensemble (NMME) using different observational data sets for verification. Results show dynamical prediction skill of the TP precipitation is regionally dependent with significantly high skills in the southwes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Second, in the valley area, the temperature drops faster on the mountain slopes at night and slower in the valley. Cold air sinks with the mountain slopes, causing the warm and wet air in the valley bottom to rise (Li et al, 2009; Wang et al, 2023; Yu et al, 2011). This makes the area an excellent research site for studying the effects of night‐time precipitation changes on surface energy and water characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Second, in the valley area, the temperature drops faster on the mountain slopes at night and slower in the valley. Cold air sinks with the mountain slopes, causing the warm and wet air in the valley bottom to rise (Li et al, 2009; Wang et al, 2023; Yu et al, 2011). This makes the area an excellent research site for studying the effects of night‐time precipitation changes on surface energy and water characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the current operational prediction skill for the TP precipitation still falls far from the expected level. For example, Wang et al (2022) demonstrated that climate models still exhibit limited skill in seasonal to inter-annual prediction for the TPSP, especially across the central-eastern TP [33]. Thus, improvements are urgently needed.…”
Section: Introductionmentioning
confidence: 99%